Propuesta metodológica para la identificación de expertos en el ámbito organizacional - Aures García, Álvaro Antonio (2022)
This article presents a methodology for identifying experts who can help any kind of organization to improve their competitiveness and facilitate innovation in project management. The proposal stems from verifying the gaps and traps generated when expert knowledge is not shared within organizations. Based on a taxonomy, the proposed methodology identifies the fields of knowledge for which an organization requires an expert. After that, it proposes criteria for identifying possible experts and assessing their expertise based on knowledge management concepts. This proposal was developed from working with various public institutions, all governing in their respective sectors, and carrying out large-scale projects.